The emergence of subjectivity in the ancient and medieval world an interpretation of western civilization - Stewart, Jon 1961- (Oxford University Press, 2020)
This volume presents a philosophical analysis of the development of Western civilization from antiquity to the Middle Ages by tracing the various self-conceptions of different cultures as they developed historically, reflecting different views of what it is to be human and the rise of the concept of subjectivity.
This edition also issued in print: 2020
Includes bibliographical references and index
Keywords: Geschichte Anfänge-1500; Subjectivity / History; Self (Philosophy) / History; Zivilisation; Subjektivität